2021
DOI: 10.1002/mrm.29089
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous comprehensive liver T1, T2, , T, and fat fraction characterization with MR fingerprinting

Abstract: fraction abdominal MR fingerprinting (MRF) approach for fully comprehensive liver-tissue characterization in a single breath-hold scan.Methods: A gradient-echo liver MRF sequence with low fixed flip angle, multiecho radial readout, and varying magnetization preparation pulses for multiparametric encoding is performed at 1.5 T. The T * 2 and fat fraction are estimated from a graph/cut water/fat separation method using a six-peak fat model. Water/ fat singular images obtained are then matched to an MRF dictionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…The "fingerprint" of every voxel is then compared against all entries included in the dictionary by pattern matching (eg, dot product or least square), to estimate the parameter combination that best represents the measured signal evolution. 49 Magnetic resonance multitasking is an alternative paradigm that can also provide multiparametric imaging. This technique captures cardiac motion, respiratory motion and relaxation parameters continuously, and can resolve the overlapping dynamics without the use of ECG triggering or breath holds.…”
Section: Magnetic Resonance Fingerprinting and Mr Multitaskingmentioning
confidence: 99%
See 1 more Smart Citation
“…The "fingerprint" of every voxel is then compared against all entries included in the dictionary by pattern matching (eg, dot product or least square), to estimate the parameter combination that best represents the measured signal evolution. 49 Magnetic resonance multitasking is an alternative paradigm that can also provide multiparametric imaging. This technique captures cardiac motion, respiratory motion and relaxation parameters continuously, and can resolve the overlapping dynamics without the use of ECG triggering or breath holds.…”
Section: Magnetic Resonance Fingerprinting and Mr Multitaskingmentioning
confidence: 99%
“…The “fingerprint” of every voxel is then compared against all entries included in the dictionary by pattern matching (eg, dot product or least square), to estimate the parameter combination that best represents the measured signal evolution. 49…”
Section: Native Techniquesmentioning
confidence: 99%
“…111 This framework was later expanded to also include simultaneous T1rho mapping, given evidence that T1rho can play a role in liver fibrosis assessment. 117,118 Velasco et al 112 found that simultaneous mapping of T1, T2, T2*, T1rho, and FF again provided comparable measurements to conventional techniques in phantoms and was feasible in vivo with excellent output of high-quality reconstructed maps. More recently, Fujita et al 13 validated MRF-derived simultaneous T1, T2, T2*, and FF maps by comparing to reference maps and to biopsy histopathology.…”
Section: Abdominal Imagingmentioning
confidence: 99%
“…Image acquisition variability and reader experience remain sources for inhomogeneity in the care received by patients in centers around the world. There is evidence that quantitative parameters can be measured for various imaging findings in the abdomen, can be used in characterization of liver disease, and can be used for therapeutic response assessment 13,104–115 . Magnetic resonance fingerprinting provides a simultaneous multiparametric rapid quantitative analysis that could be highly valuable to abdominal organ assessment.…”
Section: Current Clinical Applicationsmentioning
confidence: 99%
“…By combining multiple steady‐state acquisitions, quantitative information regarding several tissue properties can be extracted. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 However, these steady‐state approaches require a multiplicity of scans or scan‐segments, leading to scan times that are too long for clinical practice. Transient‐state sequences may overcome this downside.…”
Section: Introductionmentioning
confidence: 99%